Properties of flares and CMEs on EVLac: possible erupting filament - Muheki, Priscilla; Guenther, E. W.; Mutabazi, T.; Jurua, E. (Oxford University Press on behalf of the Royal Astronomical Society, 2020)
Flares and coronal mass ejections (CMEs) are very powerful events in which energetic radiation and particles are ejected within a short time. These events thus can strongly affect planets that orbit these stars. This is particularly relevant for planets of M-stars, because these stars stay active for a long time during their evolution and yet potentially habitable planets orbit at short distance. Unfortunately, not much is known about the relation between flares and CMEs in M-stars as only very few CMEs have so far been observed in M-stars. In order to learn more about flares and CMEs on M-stars, we monitored the active M-star EV Lac spectroscopically at high resolution. We find 27 flares with energies between 1.6 × 1031 and 1.4 × 1032 erg in Hα during 127 h of spectroscopic monitoring and 49 flares with energies between 6.3 × 1031 and 1.1 × 1033 erg during the 457 h of Transiting Exoplanet Survey Satellite (TESS) observation. Statistical analysis shows that the ratio of the continuum flux in the TESS band to the energy emitted in Hα is 10.408 ± 0.026. Analysis of the spectra shows an increase in the flux of the He II 4686Å line during the impulsive phase of some flares. In three large flares, we detect a continuum source with a temperature between 6900 and 23 000 K. In none of the flares we find a clear CME event indicating that these must be very rare in active M-stars. However, in one relatively weak event, we found an asymmetry in the Balmer lines of ∼220 km s−1, which we interpret as a signature of an erupting filament.
Keywords: Sun: coronal mass ejections (CMEs); Sun: filaments; Prominences; Sun: flares; Stars: activity; Stars: individual: EV Lac.